Galangin Inhibits Gastric Cancer Growth Through Enhancing STAT3 Mediated ROS Production - Liang, Xiaohui; Wang, Ping; Yang, Chun; Huang, Fei; Wu, Hui; Shi, Hailian; Wu, Xiaojun (Frontiers in Pharmacology, 2021)
Galangin, a flavonoid isolated from the rhizome of Alpinia officinarum (Hance), exerts anticancer activities against many cancer cells such as liver cancer, breast cancer, lung cancer and esophageal cancer. However, the effect, as well as the underlying molecular mechanism of galangin on gastric cancer remains to be elucidated. In the present study, galangin inhibited cell viability of MGC 803 cells but not normal gastric mucosal epithelial GES-1 cells. It suppressed cell proliferation accompanied by reduced Ki67 and PCNA expression, promoted apoptosis shown by decreased Bcl-2 and elevated cleaved caspase-3 and cleaved PARP. And, galangin significantly inactivated JAK2/STAT3 pathway. When STAT3 was overexpressed, the proliferation inhibition and apoptosis promotion induced by galangin were abrogated. Meanwhile, galangin increased ROS accumulation, and reduced Nrf2 and NQO-1, but elevated HO-1 in MGC 803 cells. NAC, a ROS scavenger, rescued ROS over-accumulation and proliferation inhibition of galangin. STAT3 overexpression also counteracted excessive ROS accumulation induced by galangin. Consistent with the in vitro experiments, in nude mice exnografted with MGC 803 cells, galangin inhibited tumor growth and reversed the abnormally expressed proteins, such as p-JAK2, p-STAT3, Bcl-2, cleaved caspase-3, cleaved PARP, and Ki67. Taken together, galangin was suggested to inhibit the growth of MGC 803 cells through inducing apoptosis and decreasing cell proliferation, which might be mediated by modulating STAT3/ROS axis. Our findings implicate a potential application of galangin for gastric cancer therapy possibly with low toxicity.